Glass, preparation method and application

By adjusting the composition ratio of glass and optimizing chemical composition, the problem of insufficient strength and scratch resistance performance of existing glass at low thickness is solved, and the needs of high strength and scratch resistance are met in applications such as smart terminal display screens and automotive protective glass.

CN119822634APending Publication Date: 2025-04-15HEBEI ANGRUI AUTOMATION EQUIPMENT TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510114833.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing soda-lime silicone glass cannot meet the requirements of high strength, high deformation resistance and scratch resistance at low thickness, and it is difficult to meet the needs of applications such as smart terminal display screens and automotive protective glass.

Method used

By adjusting the composition distribution ratio of the glass, the content of silica, alumina and boron oxide is increased, and sodium oxide, potassium oxide, magnesium oxide and calcium oxide are added, the grid structure and chemical composition of the glass are optimized to improve its strength, hardness and scratch resistance.

Benefits of technology

The stress strength, Vickers hardness and scratch resistance of the glass are significantly improved at low thickness, meeting the needs of applications such as smart terminal display screens and automotive protective glass, while reducing the difficulty of forming during the glass production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses glass, a preparation method and application, and relates to the technical field of glass manufacturing. Wherein the glass comprises the following components: silicon dioxide, aluminum oxide, boric oxide, sodium oxide, potassium oxide, magnesium oxide and calcium oxide; wherein the weight relation of the silicon dioxide, the aluminum oxide and the boron oxide meets a specific quantitative relation, and the weight relation of the seven components meets another specific quantitative relation. The prepared glass has high stress intensity and stress depth, and the scratch resistance and impact resistance of the glass enable the glass to meet the requirements of display equipment of an intelligent terminal and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass manufacturing, and in particular to glass, a preparation method and application thereof. Background Art

[0002] With the trend of lightweight and thin smart terminals such as mobile phones and tablets, the thickness of display components on these smart devices is required to be continuously reduced; however, the main material of display components is glass, and the strength of glass will continue to decrease as the thickness decreases. In addition, the requirements for the scratch resistance of display components are getting higher and higher. The existing soda-lime-silica glass cannot simultaneously meet the requirements of high strength, high deformation resistance and scratch resistance at low thickness. It is necessary to develop a glass with high strength, high hardness and good scratch resistance at low thickness. Summary of the invention

[0003] The main purpose of the present invention is to develop a glass, a preparation method and an application so that its strength and hardness at a relatively low thickness can meet the use requirements and can meet the requirements for the hardness and strength of glass in various application scenarios such as smart terminal display screens, automobile protective glass and windows.

[0004] To achieve the above object, the present invention provides a glass, which comprises the following components by weight percentage: silicon dioxide: 61wt% to 66wt%; aluminum oxide: 11wt% to 18wt%; boron oxide: 1wt% to 5wt%; sodium oxide: 10wt% to 15wt%; potassium oxide: 0.4wt% to 5wt%; magnesium oxide: 0.5wt% to 5wt%; calcium oxide: 0.1wt% to 2wt%; wherein the weight relationship of silicon dioxide, aluminum oxide and boron oxide is as follows: In terms of weight percentage, the following conditions are satisfied: 30.01≤0.36×SiO2+0.78×Al2O3-0.53×B2O3≤35.15; and / or, the weight relationship of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide and calcium oxide, in terms of weight percentage, satisfies: 12.28≤0.42×SiO2-0.47×(B2O3-Al2O3)-1.03×(Na2O-K2O)-2.58×(MgO-CaO)≤22.91.

[0005] In one embodiment, the glass comprises the following components by weight percentage: silicon dioxide: 61.9wt% to 65.2wt%; aluminum oxide: 12.3wt% to 17.3wt%; boron oxide: 1.6wt% to 4.3wt%; sodium oxide: 10.8wt% to 14.2wt%; potassium oxide: 1wt% to 4.2wt%; magnesium oxide: 1.1wt% to 4.2wt%; calcium oxide: 0.3wt% to 1.6wt%; wherein the weight percentage of silicon dioxide, aluminum oxide and boron oxide is The relationship between the amounts, calculated as a percentage by weight, satisfies: 31.03≤0.36×SiO2+0.78×Al2O3-0.53×B2O3≤34.69; and / or, the relationship between the weights of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide and calcium oxide, calculated as a percentage by weight, satisfies: 14.02≤0.42×SiO2-0.47×(B2O3-Al2O3)-1.03×(Na2O-K2O)-2.58×(MgO-CaO)≤21.34.

[0006] In one embodiment, the glass has a T 200 、T 35000 、T x and T S Satisfies the following relationship: 2.66≤(T 200 -T 35000 ) / (T x -T S )≤2.95; where, the T 200 The temperature corresponding to the viscosity of glass being 200 poise is T 35000 The temperature corresponding to the viscosity of glass being 35,000 poise is T x is the upper limit temperature of glass crystallization, the T S is the softening temperature of glass.

[0007] In one embodiment, the glass has a T 200 ≤1600℃.

[0008] In one embodiment, the glass has a T 35000 ≤1089℃.

[0009] In one embodiment, the glass has a T x ≤1000℃.

[0010] In one embodiment, the glass has a T S ≤827℃.

[0011] In one embodiment, the glass has a T 35000 and the T of the glass x The difference is greater than 80°C.

[0012] In one embodiment, when the thickness of the glass is 0.6 mm, the stress intensity CS value of the glass is greater than 900 MPa.

[0013] In one embodiment, when the thickness of the glass is 0.6 mm, the stress layer depth DOL value of the glass is ≥41 μm.

[0014] In one embodiment, when the thickness of the glass is 0.6 mm, the Vickers hardness value of the glass is greater than 700 HV.

[0015] The present invention also provides a method for preparing the glass, characterized in that the method for preparing the glass comprises the following steps: S10, mixing, melting, clarifying, homogenizing, molding, and annealing the components in the raw materials according to a proportion to obtain a glass intermediate; S20, cutting the glass intermediate product obtained in step S10; S30, chemically strengthening the glass intermediate product cut in step S20 to obtain the glass.

[0016] In one embodiment, in the step S20, the thickness of the glass intermediate product after cutting is controlled to be 0.02 mm to 0.6 mm.

[0017] In one embodiment, in step S30, the chemical strengthening specifically includes the following steps: The glass intermediate product after the cutting process in the step S20 is kept at 270°C~320°C for 25min~40min, and then placed in molten salt for chemical strengthening treatment, the chemical strengthening temperature is controlled to be 400°C~430°C, and the chemical strengthening time is controlled to be 0.25h~4h; wherein the molten salt includes 0~1wt% NaNO3 and 99wt%~100wt% KNO3.

[0018] The present invention also provides a display device, wherein the display device uses the glass.

[0019] The technical solution of the present invention provides a component and specific ratio of aluminosilicate glass, wherein sodium oxide, potassium oxide, magnesium oxide and calcium oxide are added to silicon dioxide, aluminum oxide and boron oxide as main components, so that the grid structure in the glass phase is strengthened; the present invention also reasonably controls the component and specific ratio of aluminosilicate glass, so that the temperature T of the glass at a specific viscosity is 200 and T 35000 And the upper limit temperature of glass crystallization T x , Glass softening temperature T SThe specific relationship is satisfied, thereby further improving the strength, hardness and scratch resistance of the glass, while also reducing the difficulty of glass molding during the glass production process; in the preparation method of the present invention, the pretreatment and chemical strengthening processes are used to promote rapid ion exchange on the glass surface and reach a certain stress layer depth, thereby further enhancing the stress intensity and stress depth of the glass, thereby enhancing the scratch resistance and impact resistance of the glass. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0022] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features limited to "first" and "second" may explicitly or implicitly include at least one of the features. In addition, if "and / or" or "and / or" appears in the full text, its meaning includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or solutions that satisfy both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0023] The technical problem solved by the present application is: with the continuous popularization of smart terminals such as mobile phones and tablet computers and the trend of thinning and lightweight development, the thickness of display components such as display screens on these smart devices is required to be continuously reduced, while the strength of glass will be greatly reduced as the thickness decreases, resulting in its fragility. The existing soda-lime-silica glass cannot simultaneously meet the requirements of low thickness and high strength, high deformation resistance and scratch resistance.

[0024] In order to solve the above technical problems, a glass is designed whose strength and hardness at low thickness can meet the requirements of smart terminal display screens, automobile protective glass, automobile windows, etc. for glass materials. The present invention proposes a glass, a preparation method and an application.

[0025] The present invention provides a glass, which comprises the following components by weight percentage: silicon dioxide: 61wt% to 66wt%; aluminum oxide: 11wt% to 18wt%; boron oxide: 1wt% to 5wt%; sodium oxide: 10wt% to 15wt%; potassium oxide: 0.4wt% to 5wt%; magnesium oxide: 0.5wt% to 5wt%; calcium oxide: 0.1wt% to 2wt%; wherein the weight relationship of silicon dioxide, aluminum oxide and boron oxide by weight percentage is The weight ratio of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide and calcium oxide, calculated by weight percentage, satisfies: 30.01≤0.36×SiO2+0.78×Al2O3-0.53×B2O3≤35.15; and / or, the weight ratio of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide and calcium oxide, calculated by weight percentage, satisfies: 12.28≤0.42×SiO2-0.47×(B2O3-Al2O3)-1.03×(Na2O-K2O)-2.58×(MgO-CaO)≤22.91.

[0026] It should be noted that the content of silicon dioxide in the glass is 61-66wt%, which can be 61wt%, 61.9wt%, 62.6wt%, 63.3wt%, 64.1wt%, 65.2wt%, 66wt%, including but not limited to the above-mentioned values. Silicon dioxide is the main body of the glass grid structure. In the technical solution of the present invention, when the content of silicon dioxide is lower than 61wt%, the glass will not be easy to form during the glass forming process, and the thermal expansion coefficient of the prepared glass will increase, the chemical corrosion resistance will decrease, and the stability will be poor; when the content of silicon dioxide is higher than 66wt%, the melting point of the glass will increase, increasing the difficulty of melting the glass during the production process. At the same time, too high a silicon dioxide content will reduce the impact resistance of the glass, which is not conducive to the production of thinner glass.

[0027] It should also be noted that the content of aluminum oxide in the glass is 11wt% to 18wt%, which can be 11wt%, 12.3wt%, 13.5wt%, 14.4wt%, 16.4wt%, 17.3wt%, 18wt%, including but not limited to the above-mentioned values. As a network modifier, the aluminum oxide tetrahedron [AlO4] with a four-coordinate structure formed by Al in aluminum oxide and non-bridging oxygen can be connected with the silicon oxide tetrahedron [SiO4], so that the original unconnected silicon oxide tetrahedron [SiO4] in the glass is connected through the aluminum oxide tetrahedron, increasing the connectivity inside the glass network, making the structure more compact, thereby improving the mechanical strength and thermal stability of the glass. The volume of aluminum oxide tetrahedron is larger than that of silicon oxide tetrahedron, and the formed glass grid structure has larger gaps, which is conducive to ion exchange and helps to improve the scratch resistance and drop resistance of the glass. It should also be noted that excessive aluminum oxide will also form an aluminum oxide octahedron [AlO6] structure. The aluminum oxide octahedron is free between the network structure and does not participate in cross-linking. Too high an aluminum oxide octahedron content will destroy the original silicon oxide network structure, reduce the stability of the glass structure, and affect its impact resistance. When the aluminum oxide content is insufficient, the glass is more susceptible to hydrolysis or acid-base erosion, and the strength and impact resistance of the glass will also be significantly reduced.

[0028] It should also be noted that the content of boron oxide in the glass is 1wt% to 5wt%; it can be 1wt%, 1.6wt%, 2.5wt%, 3wt%, 3.8wt%, 4.3wt%, 5wt%, including but not limited to the above-listed values. When the content of boron oxide is low, it mainly exists in the form of a four-coordinate structure in the glass, and as the content increases, the three-coordinate structure gradually increases. The four-coordinate structure usually exists in the form of a tetrahedron, and is connected to other units in the glass network by sharing oxygen atoms to form a tighter network structure; the three-coordinate structure usually exists in the form of a planar triangle to form a looser network structure. The four-coordinate structure accounts for more, which is beneficial to enhance the strength and hardness of the glass, while the three-coordinate structure accounts for more, so that the glass can better adapt to volume changes and reduce potential cracks during the cooling process, which is beneficial to reduce the melting point of the glass and increase the toughness of the glass. By controlling the dosage ratio of boron oxide and other components, the four-coordinate structure and the three-coordinate structure of boron oxide in the glass are in a balanced state, so that the glass of the present invention has high strength and scratch resistance at the same time under the condition of low thickness.

[0029] It should also be noted that the content of sodium oxide in the glass is 10wt% to 15wt%; it can be 10wt%, 10.8wt%, 11.6wt%, 12.7wt%, 13.2wt%, 14.2wt%, 15wt%, including but not limited to the values ​​listed above. Sodium oxide, as a network exosome, is one of the main exchange ions in the chemical strengthening process and plays a role in fluxing. On the one hand, it can reduce the melting temperature of the glass, and on the other hand, it can improve the chemical stability of the glass.

[0030] It should also be noted that the content of potassium oxide in the glass is 0.4wt% to 5wt%; it can be 0.4wt%, 1wt%, 1.6wt%, 2.8wt%, 3.7wt%, 4.2wt%, 5wt%, including but not limited to the above-mentioned values. Potassium oxide can also adjust the high-temperature viscosity of the glass during melting and the mechanical strength after molding, but unlike sodium oxide, potassium oxide does not participate in the ion exchange process. Therefore, in the later strengthening process, the main component of the molten salt is potassium oxide; excessive potassium oxide will inhibit the ion exchange of the glass, which is not conducive to improving the strength of the glass.

[0031] It should also be noted that the content of magnesium oxide in the glass is 0.5wt% to 5wt%; it can be 0.5wt%, 1.1wt%, 2wt%, 2.8wt%, 3.3wt%, 4.2wt%, 5wt%, including but not limited to the above-mentioned values. Magnesium oxide is mainly used to promote the melting of glass. Magnesium oxide can also generate a potential difference to promote ion exchange and increase the stress strength and depth of the glass. If the content of magnesium oxide is lower than 0.5wt%, it will not significantly improve the melting effect of the glass. If the content is higher than 5wt%, it will increase the viscosity of the glass liquid, promote crystallization, and reduce the transparency and toughness of the glass.

[0032] It should also be noted that the content of calcium oxide in the glass is 0.1wt% to 2wt%; it can be 0.1wt%, 0.3wt%, 0.5wt%, 1wt%, 1.2wt%, 1.6wt%, 2wt%, including but not limited to the above-listed values. Calcium oxide can reduce the crystallization tendency of glass liquid and adjust the exchange speed and depth of ions, thereby improving the chemical stability and mechanical strength of glass.

[0033] It should also be noted that the weight relationship of the silica, alumina and boron oxide, calculated in weight percentage, satisfies: 30.01≤0.36×SiO2+0.78×Al2O3-0.53×B2O3≤35.15; the silica, alumina and boron oxide in the present invention are mainly connected in a three-dimensional tetrahedral structure in the glass network structure. Through the limitation of the above quantitative relationship, the proportion of silicon oxygen tetrahedron, aluminum oxygen tetrahedron and boron oxygen tetrahedron constituting the grid body in the glass structure can reach a special balance, thereby improving the connection degree of the glass network structure and obtaining a stable glass network structure; silica is the main glass network structure, alumina preferentially allows boron oxide to enter the glass network structure, and aluminum oxygen tetrahedron can effectively shield easily polarized oxygen atoms to make them difficult to move, thereby inhibiting the precipitation of quartz.

[0034] It should also be noted that the weight relationship of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide and calcium oxide, calculated as a percentage by weight, satisfies: 12.28≤0.42×SiO2-0.47×(B2O3-Al2O3)-1.03×(Na2O-K2O)-2.58×(MgO-CaO)≤22.91; by making the components in the glass satisfy the above relationship, the glass has higher chemical stability and better crystallization performance, and can also make the glass have better chemical strengthening performance.

[0035] In one embodiment, the glass comprises the following components by weight percentage: silicon dioxide: 61.9wt% to 65.2wt%; aluminum oxide: 12.3wt% to 17.3wt%; boron oxide: 1.6wt% to 4.3wt%; sodium oxide: 10.8wt% to 14.2wt%; potassium oxide: 1wt% to 4.2wt%; magnesium oxide: 1.1wt% to 4.2wt%; calcium oxide: 0.3wt% to 1.6wt%; wherein the weight percentage of silicon dioxide, aluminum oxide and boron oxide is The relationship, calculated by weight percentage, satisfies: 31.03≤0.36×SiO2+0.78×Al2O3-0.53×B2O3≤34.69; and / or, the weight relationship of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide and calcium oxide, calculated by weight percentage, satisfies: 14.02≤0.42×SiO2-0.47×(B2O3-Al2O3)-1.03×(Na2O-K2O)-2.58×(MgO-CaO)≤21.34.

[0036] It should be noted that, during the research and development process, the inventors discovered through multiple experiments that when the content of each component in the glass changes, the CS value and Vickers hardness value of the glass produced under the condition of unchanged preparation process at low thickness have the same change trend, while the change trend of the DOL value of the glass is opposite to the former; the inventors also discovered during the research and development process that when the content of each component in the glass is further limited to satisfy the above-mentioned ratio and weight relationship, the comprehensive performance of the produced glass at low thickness is better, and at the same time has higher strength, hardness and scratch resistance.

[0037] In one embodiment, the glass has a T 200 、T 35000 、T x and T S Satisfies the following relationship: 2.66≤(T 200 -T 35000 ) / (T x -T S )≤2.95; where, the T 200 The temperature corresponding to the viscosity of glass being 200 poise is T 35000 The temperature corresponding to the viscosity of glass being 35,000 poise is T x is the upper limit temperature of glass crystallization, the T S is the softening temperature of glass.

[0038] It should be noted that, in this embodiment, M is set as the glass crystallization stability factor, M=(T 200 -T 35000 ) / (T x -T S ), the glass crystallization stability factor is usually used to evaluate the ability of glass to resist crystallization. Reasonable setting of the M value can effectively avoid unnecessary crystallization of the glass during high temperature treatment, molding process and long-term use, thereby facilitating the optimization of production process parameters. Under normal circumstances, the larger the M value, the lower the difficulty of glass manufacturing; the smaller the M value, the greater the difficulty of glass manufacturing. The numerical value of M in this embodiment is limited to a certain range, which ensures that the prepared glass has higher hardness, strength and scratch resistance at low thickness.

[0039] It should also be noted that the T of the glass in this application is 200 and T 35000 The determination method includes: referring to the standard ASTM C-965, using a rotary high temperature viscometer to measure the high temperature viscosity-temperature curve of glass, and the temperature T corresponding to the viscosity of 200P 200 , 35000P viscosity corresponds to temperature T 35000 .

[0040] It should also be noted that the T of the glass in this application is xThe determination method includes: referring to the standard ASTM C-829 and using the gradient temperature furnace method to determine the upper limit temperature of glass crystallization.

[0041] It should also be noted that the T of the glass in this application is s The measuring method includes: measuring the softening point of glass by referring to the method of standard ASTM C338.

[0042] In one embodiment, the glass has a T 200 ≤1600℃.

[0043] In one embodiment, the glass has a T 35000 ≤1089℃.

[0044] In one embodiment, the glass has a T x ≤1000℃.

[0045] In one embodiment, the glass has a T S ≤827℃.

[0046] It should be noted that by measuring the T 200 、T 35000 、T x and T S By limiting the temperature, on the one hand, the temperature corresponding to different process nodes in the glass production process can be lowered, which is beneficial to saving energy and production costs. On the other hand, it can ensure that the produced glass has higher hardness, strength and scratch resistance at a low thickness.

[0047] In one embodiment, the glass has a T 35000 and the T of the glass x The difference is greater than 80°C.

[0048] It should be noted that, when △T=T 35000 -T x , △T is usually used to indicate the safe temperature range in which glass can avoid crystallization during the molding or processing process. It can also be understood as the processing window of glass. The larger the △T, the wider the temperature range in which the glass can remain amorphous, thereby reducing the risk of defects caused by premature crystallization.

[0049] In one embodiment, when the thickness of the glass is 0.6 mm, the stress intensity CS value of the glass is greater than 900 MPa.

[0050] In one embodiment, when the thickness of the glass is 0.6 mm, the stress layer depth DOL value of the glass is ≥41 μm.

[0051] In one embodiment, when the thickness of the glass is 0.6 mm, the Vickers hardness value of the glass is greater than 700 HV.

[0052] The present invention also provides a method for preparing the glass, comprising the following steps: S10, mixing, melting, clarifying, homogenizing, molding, and annealing the components in the raw materials according to a proportion to obtain a glass intermediate; S20, cutting the glass intermediate product obtained in step S10; S30, chemically strengthening the glass intermediate product cut in step S20 to obtain the glass.

[0053] In one embodiment, in the step S20, the thickness of the glass intermediate product after cutting is controlled to be 0.02 mm to 0.6 mm.

[0054] In one embodiment, in step S30, the chemical strengthening specifically includes the following steps: The glass intermediate product after the cutting process in the step S20 is kept at 270°C~320°C for 25min~40min, and then placed in molten salt for chemical strengthening treatment, the chemical strengthening temperature is controlled to be 400°C~430°C, and the chemical strengthening time is controlled to be 0.25h~4h; wherein the molten salt includes 0~1wt% NaNO3 and 99wt%~100wt% KNO3.

[0055] It should be noted that heat preservation treatment before chemical strengthening can make the temperature distribution of glass more uniform, avoid stress concentration caused by local temperature difference, and make it easier to replace sodium ions on the surface of glass, thereby increasing the depth and efficiency of ion exchange. This helps to increase the thickness of the surface compressive stress layer of glass and enhance its impact resistance.

[0056] In a specific embodiment, the method for preparing the glass comprises the following steps: S10. According to the designed glass components, calculate the required raw materials, mix them evenly and pour them into a platinum-rhodium crucible; add a clarifier, sodium chloride, at 0.5wt% of the raw materials. Heat at 1600℃~1640℃ for 7 hours and mix evenly, take out the crucible, pour the molten glass into a preheated mold and cast it into a block. Put the formed glass block into a muffle furnace and keep it at 600℃ for 2 hours at an annealing temperature, cool it to room temperature and take it out; S20, cutting the glass intermediate product obtained in step S10; controlling the thickness of the cut glass intermediate product to be 0.02-0.6 mm; S30, placing the glass intermediate product cut in the step S20 at 270-320° C. for 25-40 minutes, and then placing the glass plate intermediate product after the insulation treatment in molten salt for chemical strengthening treatment, controlling the chemical strengthening temperature to 400-430° C., and controlling the chemical strengthening time to 0.25-4 hours; the molten salt includes 0-1wt% NaNO3 and 99-100wt% KNO3.

[0057] It should be noted that the above description of the details of the preparation method is only used to explain the content of the present invention and does not limit the protection scope of the present invention.

[0058] In addition, the present invention also provides a display device, wherein the display device uses the glass. After the display device uses the glass, it has good drop resistance, impact resistance and scratch resistance.

[0059] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.

[0060] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application can be obtained commercially. Unless otherwise specified, the methods used are all conventional methods in the art.

[0061] Related test methods: (1) Determine T according to the method of ASTM-C338 s Value; T is measured according to ASTM C-965 200 and T 35000 ; T was determined according to ASTM C-829 x ; (2) Use the Japan Orihara FSM-6000LE surface stress meter to measure the surface stress intensity CS value and surface stress depth DOL value of the glass; (3) Determine the Vickers hardness value of glass in accordance with standard GB / T4340.4-2022.

[0062] Examples 1-7 Examples 1-7 are glasses made from different raw material ratios, the difference being that the amounts of the components are different, as shown in Table 1 (unit: wt %).

[0063] Comparative Example 1 Comparative Example 1 is based on Example 1, except that the amount (weight percentage) of each component is different, as shown in Table 1 (unit: wt %).

[0064] Table 1

[0065] It can be seen from Table 1 that the mass percentage of silicon dioxide in Comparative Example 1 is 67%, which does not meet the component requirements of the present invention.

[0066] The preparation process of Examples 1-7 is the same as that of Comparative Example 1, and specifically comprises the following steps: S10. According to the designed glass components, calculate the required raw materials, mix them evenly and pour them into a platinum-rhodium crucible; add a clarifier, sodium chloride, at 0.5wt% of the raw materials. Heat at 1600℃~1640℃ for 7 hours and mix evenly, take out the crucible, pour the molten glass into a preheated mold and cast it into a block. Put the formed glass block into a muffle furnace and keep it at 600℃ for 2 hours at an annealing temperature, cool it to room temperature and take it out; S20, cutting the glass intermediate product obtained in step S10; controlling the thickness of the cut glass intermediate product to be 0.02-0.6 mm; S30, placing the glass intermediate product cut in the step S20 at 300° C. for 30 minutes, and then placing the glass plate intermediate product after the insulation treatment in molten salt for chemical strengthening treatment, controlling the chemical strengthening temperature to 400° C. and the chemical strengthening time to 4 hours; the molten salt includes 1wt% NaNO3 and 99wt% KNO3.

[0067] The parameters in the preparation process of Examples 1-7 and Comparative Example 1 are specifically shown in Table 2.

[0068] Set A = 0.36 × SiO2 + 0.78 × Al2O3 - 0.53 × B2O3; Set B = 0.42 × SiO2 - 0.47 × (B2O3 - Al2O3) - 1.03 × (Na2O - K2O) - 2.58 × (MgO - CaO); It should be noted that "SiO2", "Al2O3", "B2O3", "Na2O", "K2O", "MgO" and "CaO" in the above relationship respectively refer to the weight percentage of the corresponding components used in each embodiment or comparative example.

[0069] Table 2

[0070] The properties of the glasses obtained in Examples 1-7 and Comparative Example 1 were measured, as shown in Table 3.

[0071] Table 3

[0072] By analyzing Table 2 and Table 3, it can be found that the glass prepared according to the formula of the present invention, that is, the glass prepared in Examples 1-7, has a melting temperature T200 ≤1600℃; Forming temperature T 35000 ≤1089℃; softening point T S ≤827℃, upper limit temperature of crystallization T x ≤1000℃,△T=(T 35000 -T x )>80℃, glass stability factor 2.66≤M≤2.95. Strengthening temperature is 400℃~430℃, strengthening time is 0.25h~4h; when the thickness of the prepared glass is 6mm, the corresponding CS value is>900MPa, DOL value is>41μm, and Vickers hardness value is>700HV.

[0073] In Comparative Example 1, the weight percentage of silicon dioxide is 67% and the value of A is 36.59, which do not meet the requirements of the present invention. 200 =1611℃, T 35000 =1080℃, T S =797℃, T x =1018℃,△T=(T 35000 -T x ) = 62℃, glass crystallization stability factor M = 2.40, and the glass is difficult to produce and shape.

[0074] Embodiment 8-11 Examples 8-11 are based on Example 1, with the difference that: in step S20, the thickness of the glass is different; and, in step S30, the chemical strengthening time is different, as shown in Table 4 for details.

[0075] Table 4

[0076] By analyzing Table 4, it can be obtained that the glasses prepared in Examples 8 to 11 can simultaneously meet the requirements of a CS value of 420 MPa, a DOL value of 12 μm, and a Vickers hardness of 600 HV when the thickness is only 0.02 mm.

[0077] The above description is only an exemplary embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A glass, characterized in that: The glass comprises the following components by weight percentage: Silicon dioxide: 61wt%~66wt%; Alumina: 11wt%~18wt%; Boron oxide: 1wt%~5wt%; Sodium oxide: 10wt%~15wt%; Potassium oxide: 0.4wt%~5wt%; Magnesium oxide: 0.5wt%~5wt%; Calcium oxide: 0.1wt%~2wt%; Wherein, the weight relationship of the silicon dioxide, aluminum oxide and boron oxide, calculated by weight percentage, satisfies: 30.01≤0.36×SiO2+0.78×Al2O3-0.53×B2O3≤35.15; And / or, the weight relationship of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide and calcium oxide, calculated in weight percentage, satisfies: 12.28≤0.42×SiO2-0.47×(B2O3-Al2O3)-1.03×(Na2O-K2O)-2.58×(MgO-CaO)≤22.

91.

2. The glass according to claim 1, characterized in that The glass comprises the following components by weight percentage: Silicon dioxide: 61.9wt%~65.2wt%; Alumina: 12.3wt%~17.3wt%; Boron oxide: 1.6wt%~4.3wt%; Sodium oxide: 10.8wt%~14.2wt%; Potassium oxide: 1wt%~4.2wt%; Magnesium oxide: 1.1wt%~4.2wt%; Calcium oxide: 0.3wt%~1.6wt%; Wherein, the weight relationship of the silicon dioxide, aluminum oxide and boron oxide, calculated by weight percentage, satisfies: 31.03≤0.36×SiO2+0.78×Al2O3-0.53×B2O3≤34.69; And / or, the weight relationship of the silicon dioxide, aluminum oxide, boron oxide, sodium oxide, potassium oxide, magnesium oxide and calcium oxide, calculated in weight percentage, satisfies: 14.02≤0.42×SiO2-0.47×(B2O3-Al2O3)-1.03×(Na2O-K2O)-2.58×(MgO-CaO)≤21.

34.

3. The glass according to claim 1, characterized in that The glass T 200 , T 35000 , T x and T S The following relations are satisfied: 2.66≤(T 200 -T 35000 ) / (T x -T S )≤2.95; In the formula, the T 200 The temperature corresponding to the viscosity of glass being 200 poise is T 35000 The temperature corresponding to the viscosity of glass being 35,000 poise is T x is the upper limit temperature of glass crystallization, the T S is the softening temperature of glass.

4. The glass according to claim 3, characterized in that The glass T 200 ≤1600℃; and / or, the glass has a T 35000 ≤1089℃; and / or, the glass has a T x ≤1000℃; and / or, the glass has a T S ≤827℃.

5. The glass according to claim 3, characterized in that The glass T 35000 and the T of the glass x The difference is greater than 80°C.

6. The glass according to claim 1, wherein: When the thickness of the glass is 0.6 mm, the stress strength CS value of the glass is greater than 900 MPa; And / or, when the thickness of the glass is 0.6 mm, the stress layer depth DOL value of the glass is ≥ 41 μm; And / or, when the thickness of the glass is 0.6 mm, the Vickers hardness value of the glass is greater than 700 HV.

7. A method for preparing the glass according to any one of claims 1 to 6, characterized in that: The method for preparing the glass comprises the following steps: S10, mixing, melting, clarifying, homogenizing, molding, and annealing the components in the raw materials according to a proportion to obtain a glass intermediate; S20, cutting the glass intermediate product obtained in step S10; S30, chemically strengthening the glass intermediate product after the cutting process in step S20 to obtain the glass.

8. The method for preparing glass according to claim 7, characterized in that: In the step S20, the thickness of the glass intermediate product after cutting is controlled to be 0.02 mm to 0.6 mm.

9. The method for preparing glass according to claim 7, characterized in that: In step S30, the chemical strengthening specifically includes the following steps: The glass intermediate product cut in step S20 is kept at 270° C. to 320° C. for 25 min to 40 min, and then placed in molten salt for chemical strengthening treatment, wherein the chemical strengthening temperature is controlled to be 400° C. to 430° C., and the chemical strengthening time is controlled to be 0.25 h to 4 h; Wherein, the molten salt includes 0-1wt% NaNO3 and 99wt%-100wt% KNO3.

10. A display device, characterized in that: The display device uses the glass according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Alkaline aluminosilicate protective glass capable of realizing ion exchange and preparation method thereof

    CN106698928A

  • Glass composition and strengthening method thereof

    CN108101362A

  • Aluminosilicate glass and tempered glass

    CN108503213A

  • Anti-blue-light high-strength lithium-aluminum-silicon cover plate glass and preparation method and application thereof

    CN113121109A

  • Boron aluminum silicate glass and preparation method thereof

    CN116102255A